The Role of Sport Campaigns in Shaping Sustainability Narratives: A Critical Discourse Analysis - Sabri Breesam, Sura; Abd Hasan, Bushra (Program Studi Tadris Bahasa Inggris Sekolah Tinggi Agama Islam Negeri Mandailing Natal, 2025)
This research examines environmental discourse within sports, focusing on its linguistic, discursive, and social aspects. The analysis elucidates the construction of environmental discourse in sports through three primary stages: production, distribution, and consumption, emphasizing the interplay of sports firms, environmental organizations, and the public in producing environmental narratives. It underscores the influence of economic and political forces in utilizing the notion of sustainability for marketing and ideological objectives while accentuating the significance of grassroots activities in countering these prevailing narratives. This study employs critical discourse analysis (CDAhenceforth) to examine verbal and visual elements of sports ads. The researchers selected ten social media advertisements in English and Arabic that promote sustainability in sports. Data was gathered from multiple media platforms, encompassing social media initiatives. The research examines advertisements published from 2020 to 2025, using sports businesses or events, sustainability themes, and endorsements by athletes. Sports discourse emphasizes the significance of sustainability in business reputation and environmental accountability. Sustainability is perceived as a progressive endeavor necessitating continuous dedication, surpassing mere marketing fads. Sports foster environmental awareness via text creation, dissemination, and consumption, and can function as a marketing tactic. Sports discourse underscores sustainability in corporate branding and environmental accountability, surpassing marketing trends.